Improving Students' Mathematical Communication Through Differentiated Learning Implementing the MERDEKA Class VII Flow - Frildawati, Dinda; Izzati, Nur; Syani Putri, Nurul Hilda (Jurnal Cendekia : Jurnal Pendidikan Matematika, 2024)
Students' mathematical communication abilities are crucial for acquiring mathematical concepts during mathematics learning. The MERDEKA route offers differentiated learning and is an excellent tool for helping students develop these abilities. This research aims to determine how much-differentiated learning can be contributed by applying the MERDEKA pathway to enhance students' mathematical communication skills. This type of research is Quasi-Experimental with a pretest-posttest control group design. The sample for this research was students of class VII-D and class VII-F, who were selected using cluster sampling techniques from all class VII of SMPN 5 Tanjungpinang. The Independent Sample T-test was used to analyze the data at a 5% significance level. According to this study, students' mathematical communication abilities increase through differentiated learning using the MERDEKA route rather than regular group learning techniques.